ChemInform Abstract: A Facile and Efficient Method for the One‐Pot Synthesis of Per‐O‐Acetylated Thioglycosides from Unprotected Sugars. Issue 17 (4th April 2013) - Yan, Shiqiang; Ding, Ning; Zhang, Wei; Wang, Peng; Li, Yingxia; Li, Ming
Abstract Acetylation of various unprotected sugars, including 2‐deoxy‐2‐amino sugars, sialic acid, lactose, and maltose, with a stoichiometric amount of acetic anhydride followed by thioglycosidation with thiocresol furnishes the corresponding thioglycosides in good to high yield under solvent‐free conditions.